Asymetric Pass-through Effects of Oil Price Shocks and Exchange Rates on Inflation in Nigeria: Evidence from a Nonlinear ARDL Model - Sa’ad, Suleiman; Usman, Ali Baba; Omaye, Solomon Ochada; Yau, Hamisu (European Scientific Journal, ESJ, 2023)
By utilizing the non-linear ARDL (NARDL) model developed by Shin, et al (2014), we examined the asymmetric effect of oil price and exchange rates pass-through on inflation in Nigeria over a period of 1970 to 2020. Result of asymmetric test revealed the existence of asymmetries among the variables of the study, suggesting that there is a nonlinear interaction among the variables used in the study. This validates the choice of non-linear ARDL model for the study. Result of the long-run estimates show that rising (Positive) oil price shocks have a greater impact on inflation than falling (negative) oil price shock. Furthermore, ot is evident form the result that depreciation of exchange rate has much and significant effect on inflation than the appreciation of exchange rate in Nigeria. However, rising interest rate increases inflation by 0.84 per cent while falling interest rate increases inflation by 0.85 per cent. This implies that the effect of negative interest rate on inflation is higher than its positive effect on inflation, though, by a smaller amount of about 0.01 per cent. Again, the short-run dynamic model revealed a high speed of convergence of more than 90% from the short run disequilibrium. During the study period, the oil price fluctuations showed a significant and incomplete pass-through to both exchange rates and inflation in Nigeria. Based on the findings, the study recommends policies that set oil prices and exchange rate within reasonable limits in order to chack inflation in Nigeria.